Comparison of Three Electrical Resistivity Arrays to Investigate Weak Zones in Soil, Along a Profile Southeast Baghdad City, Iraq - Al-Saady, Hussein Abdulrahim; Karim, Hussein H.; AL-Menshed, Firas H. (Iraqi Journal of Science, 2022)
The electrical resistivity method is one of the geophysical methods for detecting weak subsurface zone. The 2D resistivity data were used to compare three electrode configurations, Wenner, Dipole-dipole, and Schlumberger, to detect weak subsurface zones along a profile south of Baghdad near the Bismayah pumping station. The results show many zones of low resistivity that may be weak zones. A dipole-dipole array is a large number of measurements and is more sensitive than others. The Wenner-Schlumberger array has a depth also higher than other arrays. Wenner array has higher signal strength than other arrays. Because it is more sensitive to horizontal and vertical structures, the dipole-dipole array is the optimum for mapping subsurface weak zone.